2015
DOI: 10.17716/botkozlem.2015.102.1-2.141
|View full text |Cite
|
Sign up to set email alerts
|

The role of seed banks in sustaining alkali grassland biodiversity in the Hortobágy National Park, Hungary

Abstract: Kulcsszavak: abiotikus stressz, halofi ton, higrofi ton, magkészlet, sótartalom. Összefoglalás:A pannon szikes gyepek a Natura 2000 hálózatban kiemelt közösségi jelentőségű élőhelyek. Megőrzésükért az Európai Unióban nagy felelősség hárul Magyarországra, mert hazánkban található az európai állományok 98%-a. Vizsgálatunkban a vertikális pozíció és a környezeti változók (nedvességtartalom, sótartalom, pH, humusz és kötöttség) szerepét tanulmányoztuk a felszín feletti vegetáció és a talajmagbank fajösszetételére.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The mechanism of storage and evaporation is completely unknown in the world of physiology. At the end of the last millennium, water transport experiments on Sikfőkút were a milestone in physiological research, involving several famous institutions and universities were involved [9]. Without being exhaustive ATOMKI Budapest, Hungary, DOTE Debrecen, Hungary, University of Marburg, IATA Florence, University of Forestry and Woodworking Sopron, Hungary.…”
Section: How the Water Pump Work?mentioning
confidence: 99%
“…The mechanism of storage and evaporation is completely unknown in the world of physiology. At the end of the last millennium, water transport experiments on Sikfőkút were a milestone in physiological research, involving several famous institutions and universities were involved [9]. Without being exhaustive ATOMKI Budapest, Hungary, DOTE Debrecen, Hungary, University of Marburg, IATA Florence, University of Forestry and Woodworking Sopron, Hungary.…”
Section: How the Water Pump Work?mentioning
confidence: 99%
“…Firstly, environmental conditions at the clearing sites are preferable for the more light-demanding weed species. Secondly, it has been found that in several grassland types most of the characteristic species have only sporadically persistent seed banks [44,45]. The total seed density proved to be variable, which is also true of most natural and semi-natural habitats [46].…”
Section: Seed Bank Composition and Densitymentioning
confidence: 99%